Review of Adaptation and Histopathological Changes of the Fish Respiratory System to Parasites and Diseases - Aisyah, Aisyah; Andriani, Yuli (Aquaculture Department, University of Mataram, 2024)
The respiratory system of fish is particularly susceptible to parasitic infections and diseases that can cause significant histopathological changes. This article discusses the adaptation of fish's respiratory system to environmental stresses caused by parasites and pathogens, as well as the histopathological changes that occur in response to infection. Some of the major changes observed include hyperplasia, hypertrophy, necrosis, and edema of the tissues in the gills, which can affect the respiratory function of the fish. In addition, granuloma formation and increased mucus production were also noted as adaptive responses to parasitic infections. Although some histopathological changes can improve the fish's body defenses, the tissue damage that occurs as a result of chronic infections can lead to serious impaired respiratory function and decrease the survival of fish. Understanding the mechanisms of adaptation and histopathological changes is very important for fish health management, especially in aquaculture, in order to reduce the negative impact of diseases and increase fish productivity.